2015
DOI: 10.1155/2015/740315
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Activation of Vastus Medialis Oblique and Vastus Lateralis in Sling-Based Exercises in Patients with Patellofemoral Pain Syndrome: A Cross-Over Study

Abstract: Objectives. To examine what changes are caused in the activity of the vastus medialis oblique (VMO) and vastus lateralis (VL) at the time of sling-based exercises in patients with patellofemoral pain syndrome (PFPS) and compare the muscular activations in patients with PFPS among the sling-based exercises. Methods. This was a cross-over study. Sling-based open and closed kinetic knee extension and hip adduction exercises were designed for PFPS, and electromyography was applied to record maximal voluntary contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 29 publications
0
16
0
1
Order By: Relevance
“…An over-active TFL can put lateral force on the patella through connections to the iliotibial band [13,14]. This movement pattern has been associated with PFPS and ITBS syndrome [9,[14][15][16][17]. Also, the current investigation is based on the premise that excessive activation of the TFL may be counterproductive in the treatment of subjects with GVD, during therapeutic exercises in which excessive hip medial rotation may be a contributing factor [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An over-active TFL can put lateral force on the patella through connections to the iliotibial band [13,14]. This movement pattern has been associated with PFPS and ITBS syndrome [9,[14][15][16][17]. Also, the current investigation is based on the premise that excessive activation of the TFL may be counterproductive in the treatment of subjects with GVD, during therapeutic exercises in which excessive hip medial rotation may be a contributing factor [8].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it would be necessary to promote the GMed activity as minimizing TFL activation [8]. The strength imbalance between the vastus medialis (VM) and vastus lateralis (VL) [14] that occurs due to knee malalignment in GVD shifts the patella laterally, and has led some authors to suggest that this strength difference is associated with PFPS syndrome [15,16].…”
Section: Gvdmentioning
confidence: 99%
“…By contrast 41 stated that application of sling open chain knee extension (SOCKE) exercise in conjunction with sling exercise therapy (SET) intensified VMO activity compared to VL activity. Most of the studies that were reviewed compared the responses of the VMO and VL muscles of participants with PFPS 42 to open and closed kinetic chain exercises, but none of them compared experimental and placebo control groups.…”
Section: Analysis Of Reviewed Studiesmentioning
confidence: 99%
“…[ 3 ] The patellar cartilage was worn continuously through abnormal patellar tracking, producing patellar pain, instability, and dysfunction. [ 4 ] Rehabilitation treatment for PFPS had focused on VMO muscle strengthening to correct patellar malalignment. [ 5 ] A previous study reported that specific exercise activities focusing on VMO muscle training were effective in pain reduction and functional ability improvement in patients with PFPS.…”
Section: Introductionmentioning
confidence: 99%